Ex-Corpus Christi, TX, Firefighter, Turned Manager of The Firefighters Baseball Team, Returns Home. (Firehouse, 2026)
Valerie Perez, a retired firefighter and manager of The Firefighters, experienced an emotional return to her hometown of Corpus Christi during a special Banana Ball weekend.